Julio Escámez Production, persecution and exile (1970-1974) - Lama-Andrade, Bárbara Elena (2026)
This article reviews in historical terms the participation of Julio EscámezCarrasco in the Chilean artistic field during the government of SalvadorAllende and the vicissitudes he suffered after the civic-military coup of1973. We propose an approach to his work emphasizing his networks ofsociability since he was a leftist artist who actively participated in theofficial scene and operates in the tensions between art and politics of thetime. The analysis of the creation, reception and destruction of his muralPrincipio y fin, his proposals and projects at the University of Concepción,as well as the conditions for his exile in Costa Rica allows us to understandthe magnitude of the violence that the breakdown of democracy entailedand the memory difficulties generated by his trauma.